Injury prevention and health promotion: A global perspective - Franklin, Richard C.; Sleet, David A. (Health promotion journal of Australia, 2018)
Since its inception 27 years ago (1990), the Health Promotion Journal of Australia has featured many articles on aspects of injury prevention, particularly noticeable during the past five years. With this issue, it will be only the second time the journal has launched a Special Issue on injury prevention, the first one appearing in Volume 1, issue 2, in 1991.1 As editors of the current issue, we felt the dedicated emphasis on injury prevention and health promotion in the journal is long overdue, given that our careers in injury prevention have changed considerably since the first Special Issue was published (and that a new cadre of health promotion professionals have entered the field). Therefore, we believe it is timely and important to feature some of the recent research focusing on injury prevention and health promotion.